Johnson's World: on Mercator's projection. - Johnson and Ward (Johnson and Ward, 1865)
Map shows major cities, political divisions, and physical features for six continents and a portion of the Antarctic Continent. Relief shown by hachures. Scale [ca. 1:65,200,000].